A patient with glycogen storage disease type 0 and a novel sequence variant in GYS2: a case report and literature review. Issue 8 (August 2020) - Arko, Janez Jan; Debeljak, Marusa; Tansek, Mojca Zerjav; Battelino, Tadej; Groselj, Urh
Glycogen storage disease type 0 (GSD0) is an autosomal recessive disorder caused by a sequence variant in the GYS2 gene, leading to decreased or absent activity of hepatic glycogen synthase. With a frequency of less than 1 in 1, 000, 000 individuals, GSD0 represents only around 1% of all glycogen storage disease cases but it might be underrecognized. A 13- month- old girl of reportedly unrelated parents presented with a decreased level of consciousness, twitching in her left cheek, and munching. During a fasting test, hyperketotic hypoglycemia was found. A novel homozygous GYS2 gene sequence variant p.Thr445Arg was later confirmed by next-generation gene sequencing. After establishing a cornstarch- and protein-rich diet, the hypoglycemic episodes subsided and the patient's neurocognitive development was normal. To date, only 39 patients with 24 disease-causing gene variants have been identified in GSD0, and we review their characteristics. Because of the heterogeneous phenotypes, GSD0 is an underdiagnosed disorder. In patients with hyperketotic hypoglycemia and postprandial hyperglycemia, GYS2 gene analysis should be performed.